Aggregate development effectiveness and externally-valid extrapolation: a fourth principle for Agency-Wide Performance Measurement Systems?. Issue 2 (3rd April 2021) - Garbero, Alessandra
ABSTRACT: Through Alignment, Attribution and intelligent Aggregation, the three core principles forming the basis of Agency-Wide Performance Measurement Systems, performance measurement systems that use impact assessments can make serious contribution to both accountability and lesson-learning. In this paper, we argue that Agencies would benefit by adding a fourth principle, namely ' externally-valid extrapolation ', since Agencies should be concerned about obtaining rigorous impacts estimates that can be conducive to aggregate impact predictions. Extrapolation essentially means determining a metric of aggregate development effectiveness. Ensuring externally valid extrapolation requires that this metric is estimated based on a sufficiently large set of internally valid studies accompanied by an impact assessment research programme conceived within a framework that maximises external validity at portfolio level. We show how as part of the first impact assessment initiative at IFAD, which dates back to 2012, a methodology was devised to measure and project aggregate development effectiveness at portfolio level.